Replication Data for: Association between generalized joint hypermobility, temporomandibular joint hypertranslation and temporomandibular disorders - Braga, Samilla Pontes (2025)
The scoping review aimed to address the association between GJH, TMJ hypertranslation and TMD. As a secondary aim, the lack of consensus on the diagnosis of TMJ hypertranslation was highlighted. A search was carried out across PubMed, SciELO, LILACS and Science Direct utilizing the Medical Subjective Headings (MeSH) terms “temporomandibular joint disorders”, “temporomandibular joint”, “joint instability” and “joint dislocations”. The non-indexed terms “TMJ hypermobility” and “TMJ subluxation” were used as individual searches in the same databases. The manual search was carried out in selected works through cross-referencing of the included studies and books. Furthermore, a search was carried out in the grey literature. Eligibility criteria focused on book sections, clinical trials (including randomized controlled trials), meta-analyses, multicenter studies, observational studies, and reviews (including systematic reviews) published in English between 1964 and 2024. Articles and book sections that addressed the study of clinical and imaging signs of TMJ hypertranslation and diagnostic criteria for TMJ hypermobility disorders, as TMJ subluxation, as well. . Extracted variables included demographic characteristics of participants, such as age and type of joint hypermobility diagnosis (general or TMJ localized), in addition to the extraction of data on diagnostic criteria for GJH (e.g., the Beighton test) as well as for the diagnosis of TMJ hypertranslation (anamnestic, clinical, and imaging criteria). The data extracted in this review are of a mixed nature, including quantitative information, such as diagnostic criteria and demographic characteristics of the participants, and qualitative information, such as clinical descriptions and anamnestic criteria for the diagnosis of TMJ hypertranslation.